Manejo integrado de florestas umidas neotropicais por industrias e comunidades: aplicando resultados de pesquisa, envolvendo atores e definindo politicas publicas: Simposio Internacional da IUFRO, Belem PA, Brazil, 4-7 Decembre, 2000 - Sabogal, C.; Macedo Silva, J.N. (CIFOR and Embrapa Amazonia Oriental, 2002)
The book includes a selection of 37 contributions (all in the original language - 16 in Portuguese, 13 in English and 8 in Spanish - but with abstracts in English) presented to the International Symposium “Integrated Management of Neotropical Rainforests by Industries and Communities: Applying Research Results, Involving Stakeholders and Defining Policy”, held in Belem, Brazil, from December 4 - 7 , 2000. The symposium intended to contribute - by providing information and recommendations – to the efforts underway at different levels (local, national, regional) to improve the perspectives for a wider adoption of sustainable forest management in the neotropics. The papers are divided in the three themes of the Symposium: Industrial-scale forest management (16 contributions), Community forest management and extrativism (15) and Means to promote the adoption of sustainable forest management (6). Overall, the papers provide a wide variety of conceptual, methodological and technical aspects related to the planning and implementation of forest management under different conditions, as well as practical experiences, research results and recommendations to improve the quality of forest management by different actors.